The objective of this research was to analyze the physical and mechanical properties of palm oil trunk. The result showed that in term of the vertical direction the lower part of stem had better physical (density, moisture content and shrinkage) and mechanical (modulus of elasticity, modulus of rupture, hardness, compressive and tensile strength parallel to grain) properties compared with medium and upper end part. In the horizontal direction the edge part of trunk had better physical and mech - Apri Heri ISWANTO; Tito SUCIPTO; Irawati AZHAR; Zahrial COTO; Fauzi FEBRIANTO (Departemen Hasil Hutan, IPB, 2010)
The objective of this research was to analyze the physical and mechanical properties of palm oil trunk. The result showed that in term of the vertical direction the lower part of stem had better physical (density, moisture content and shrinkage) and mechanical (modulus of elasticity, modulus of rupture, hardness, compressive and tensile strength parallel to grain) properties compared with medium and upper end part. In the horizontal direction the edge part of trunk had better physical and mechanical properties than medium and center part. Keywords : horizontal direction, palm oil stem, physical pro-perties, mechanical properties, vertical direction